The Seasonal Fluctuation of Fatigue in Multiple Sclerosis - Grothe, Matthias; Gross, Stefan; Süße, Marie; Strauss, Sebastian; Penner, Iris Katharina (Frontiers in Neurology, 2022)
Background: Fatigue is a common symptom in patients with multiple sclerosis. Several studies suggest that heat can impact fatigue severity, but we lack a systematic investigation of seasonal fluctuations. Methods: Fatigue was assessed with the Fatigue Score for Motor and Cognition (FSMC). This study included 258 patients with multiple sclerosis from 572 visits temporally distributed over the year. The data were adjusted for age, sex, cognition, depression, disease severity, and follow-up time. Linear regression models were performed to determine whether the temporal course of fatigue was time-independent, linearly time dependent, or non-linearly time dependent. Results: Fatigue was lowest during January (mean FSMC: 49.84) and highest during August (mean FSMC: 53.88). The regression analysis showed the best fit with a model that included months + months², which was a non-linear time dependency. Conclusion: In multiple sclerosis, fatigue showed a natural temporal fluctuation. Fatigue was higher during summer compared to winter. This finding should be carefully taken into account when monitoring multiple sclerosis.